Constitutive equation and model validation for a 31 vol.% B4Cp/6061Al composite during hot compression. Issue 10 (October 2018) - Zhou, L.; Cui, C.; Wang, Q.Z.; Li, C.; Xiao, B.L.; Ma, Z.Y.
Abstract: An accurate constitutive equation is essential to understanding the flow behavior of B4 C/Al composites during the hot deformation. However, the constitutive equations developed previously in literature are generally for low strain rate deformation. In the present work, we modified the general constitutive equation and take the high strain rate correction into account. The constitutive equation for a 31 vol.% B4 Cp/6061Al composite was constructed based on the flow stresses measured during isothermal hot compression at temperatures ranging from 375 to 525 °C and strain rates from 0.01 to 10 s −1 . The experimental flow stresses were corrected by considering temperature-dependent Arrhenius factor. The modified equation was then verified by using DEFORM-3D finite element analysis to simulate the experimental hot compression process. The results show that the modified equation successfully predicts flow stress, load–displacement, and the temperature rise. This helps to optimize the hot deformation process, and to obtain desirable properties, such as reduced porosity and homogenous particle distribution in B4 C/Al composites.